Facebook.com text: Industrialising personal data production - Patelis, Korinna (My University, 2013)
This article examines Facebook.com as a cultural text. It casts a critical eye on the stories told by the Facebook monopoly interphase, focusing on how these intergrate commerce with communications. It struggles with the text's key abstractions arguing that Facebook industrialises personalised data production by demanding the constant production on customised communcation objects.
Keywords: Facebook; Communications